ANALISIS PERMINTAAN IKAN SEGAR DI DAERAH ISTIMEWA YOGYAKARTA - Rr. Tri Gunartiningrum (Universitas 17 Agustus 1945 Samarinda, 2011)
ANALISIS PERMINTAAN IKAN SEGAR DI DAERAH ISTIMEWA YOGYAKARTADemand Analysis of fresh fish in Daerah Istimewa YogyakartaRr. Tri GunartiningrumSekolah Tinggi Ilmu Pertanian (STIPER) Kutai TimurSangatta ABSTRACTFish are the source of animal protein which are needed by human beings for their intellectual growth and development, especially for who are still in the growth period. The demand of fish is more increasing within society’s awareness to consume food with hight nutritious and protein. This research was aimed to identity: 1) factor influencing the demand of fresh fish 2) commodities which have substitution and complementary relation toward demand of fresh fish and 3) trend of fish’s demand in 2003-2007 inDaerah Istimewa Yogyakarta. The research employed basic descriptive analysis. The secondary data of time series were collected from many sources. The multiple regression was used to analyse factor that influenced demand of fresh and trend analysis was used to know trend of demand. Research results showed factors influencing demand fresh-water fish are: socienty’s income, number of household’s head, price of fresh-water fish, price of salt-water fish, price of chiken, and price of rice. Factors influencing the demand of salt-water fish were number of household’s head price of fresh-water fish, price of salt-water fish and price of chiken. Based on the trend analysis, it was found that for the next five years, the demand of fish in Daerah Istimewa Yogyakarta will get more increasing.Key words : Demand, Substitution, Complementary.